Social Media Marketing And Brand Image As Determinant Patient Loyalty Wit Trust As Intervening - Indri Agustin; Budi Santoso; Feti Fatimah (UNIVED Press, 2026)
Purpose – Using patient trust as an intervening variable, the study intends to investigate and assess the direct and indirect effects of social media marketing and brand image on patient loyalty. Novelty – This study examines how social media marketing and brand image affect patient loyalty using an intervening test model (patient trust). Method – This study employs an explanatory/confirmatory design. The group consisted of outpatients from Jember Regency's Dr. Soebandi Regional General Hospital. Purposive and accidental sampling were used as the sampling techniques, and the number of samples was calculated using the Slovin formula. Partial Least Square (PLS) data analysis was performed using the WarpPLS 7.0 program. Findings – The results demonstrate that patient trust is greatly impacted by social media marketing and brand image. While company image has little bearing on patient loyalty, social media marketing has a substantial impact. Patient loyalty is positively and significantly impacted by patient trust. Patient loyalty is greatly impacted by social media marketing and brand image, with patient trust acting as an intervening variable. Limitations and Implications – The results of this study cannot be broadly applied because the research participants were restricted to patients at Dr. Sobeandi Regional Hospital in Jember. Future studies might use a larger population (national or regional). An additional constraint pertains to the requirement for a survey that integrates qualitative elements to elucidate the ways in which social media marketing impacts patient loyalty and trust.